2022
DOI: 10.1136/bjsports-2021-104451
|View full text |Cite
|
Sign up to set email alerts
|

Progression through return-to-sport and return-to-academics guidelines for concussion management and recovery in collegiate student athletes: findings from the Ivy League–Big Ten Epidemiology of Concussion Study

Abstract: ObjectiveTo examine the progression of collegiate student athletes through five stages of a return-to-activity protocol following sport-related concussion (SRC).MethodsIn a multisite prospective cohort study, we identified the frequency of initial 24–48 hours physical and cognitive rest, and the sequence of (1) symptom resolution and return to (2) exertion activity, (3) limited sport, (4) full sport and (5) full academics. In resulting profiles we estimated the likelihood of return to full sport ≤14 days or pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This study also found that SRC was observed in soccer, basketball, rugby, and ice hockey, which were listed as the sports with the highest incidence of SRC in previous studies. However, rugby and ice hockey, which have been reported to have a high incidence of SRC in previous studies [ 10 , 11 , 19 ], did not rank high with regard to the number of SRC cases in Japan, whereas judo, baseball, and kendo did rank high, yielding a different result from other countries.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This study also found that SRC was observed in soccer, basketball, rugby, and ice hockey, which were listed as the sports with the highest incidence of SRC in previous studies. However, rugby and ice hockey, which have been reported to have a high incidence of SRC in previous studies [ 10 , 11 , 19 ], did not rank high with regard to the number of SRC cases in Japan, whereas judo, baseball, and kendo did rank high, yielding a different result from other countries.…”
Section: Discussionmentioning
confidence: 65%
“…A study analyzing data from the National Collegiate Athletic Association (NCAA) in the United States reported that the incidence of SRC was higher in men’s wrestling, men’s ice hockey, women’s ice hockey, and men’s football than in other sports [ 10 ]. Furthermore, a survey on SRC limited to contact sports and collision sports reported that most SRCs occurred in men’s football, women’s rugby, men’s ice hockey, men’s wrestling, and women’s soccer [ 11 ]. These studies suggest that SRC may occur frequently in sports with a high frequency of contact, thereby also garnering attention as a research subject.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence identified on RTA protocols comprised six studies: one RCT, 111 one prospective cohort study, 112 one retrospective cohort study, 113 two prospective case series, 23,114 and one retrospective case series. 115 The studies involved RTA protocols in adolescents with acute concussion.…”
Section: Rta Protocolmentioning
confidence: 99%